Good Practices in Occupational Health and Safety: A Case Study on Productive Sector Ecuador - Alberto Litardo Velásquez, Carlos; Joaquin Zambrano Ortiz, Denis; Rafael Jarre Vera, Gilberto; Fabricio Garcia Castro, Wilmer (International Journal of Psychosocial Rehabilitation, 2020)
Good practices in occupational health and safety focus on determining optimal tasks to guarantee accident prevention. The intention of the research was to detect the management carried out in Ecuador, in terms of occupational safety and health to establish strategies that allow improvement to the process. The study was presented with a documentary design. The ergonomic methods applied are Reba and Rula, which should allow exemplifying the situation in the jobs with greater accident rate. Regarding the definition of strategies, this was executed with a matrix of internal and external factors, obtaining interesting and feasible results, such as the use of technology to perform physical and risk dysergonomic assessments in the workplace, it is proposed the planning of training that lead to the application of good practices in occupational health and safety, as well as the evaluation of the strategies proposed in short and medium periods in order to determine possible deviations and continue with the process of continuous improvement within the subject.